Tahfidz Entrepreneur Teaching System at Hidayatul Arifin Islamic Boarding School Sawocangkring Wonoayu Sidoarjo: Sistem Pengajaran Tahfidz Entrepreneur di Pesantren Hidayatul Arifin Sawocangkring Wonoayu Sidoarjo - Ikwandi , Muhamad Ripin; Baihaqi , Muhammad; Handayani, Puspita; Hariyadi, Ahmad (Universitas Muhammadiyah Sidoarjo, 2023)
Hidayatul Arifin Islamic Boarding School (Hidar) Sawocangkring Wonoayu Sidoarjo is a boarding school that has 3 programs, namely the Entrepreneur Program, the Yellow Book Study Program, and the Tahfidz Al-Qur'an Program. The purpose of this study was to determine the Al-Qur'an tahfidz learning system at Hidayatul Arifin Islamic Boarding School and to find out the supporting and inhibiting factors of the tahfidz learning system. This research method uses a qualitative descriptive research method. In qualitative research, the results of written documentation, interviews and other sources such as: scientific journals, archival sources and documents are taken. The results showed that the tahfidz learning system at the Hidayatul Arifin Islamic Boarding School was to produce students who had an understanding of the yellow book, hafidz Al-Qur'an and Entrepreneurs. The tahfidz teachers who teach tahfidz at the Hidayatul Arifin Islamic Boarding School are hafidz who also understand the book of the Salaf. The learning media used by the Hidayatul Arifin Islamic Boarding School are print media and audio-visual media. Furthermore, the learning methods used by the Hidayatul Arifin Islamic Boarding School are the Bin-Nazhar method, the Talaqqi method, and the Poetry Method.